Manajemen Penerimaan Peserta Didik Baru Melalui Sistem Zonasi Dalam Meningkatkan Mutu Sekolah Di Sma Negeri 2 Palopo - Nurhalisa; Nursaeni; Dodi Ilham; Baderiah; Kaharuddin; Tasdin Tahrim (Hikamatzu | Journal of Multidisciplinary, 2024)
This thesis discusses the management of new student admissions in the zoning system in improving the quality of schools at State High School 2 Palopo. The objectives of this study are: to find out the form of application of the zoning system in improving the quality of schools at State High School 2 Palopo; stakeholder response through the implementation of the zoning system in improving the quality of schools at State High School 2 Palopo; obstacles to stakeholders through the implementation of the zoning system in improving the quality of schools at State High School 2 Palopo. The research method used is to use a descriptive qualitative approach, using data collection techniques such as observation, interviews, and document review. The technical data analysis taken is data reduction, data presentation and conclusion drawn. The subjects of this study are the principal, PPDB Committee, teachers and students. The results of this study show that: (1) The form of implementation of the zoning system in improving school quality shows a systematic process from planning to evaluation. The planning process begins with socialization to schools in the zone to find out the procedures for accepting new students in the zoning system, preparing resources optimally and planning is carried out annually according to the technical instructions of the provincial government. The organizing process is carried out by forming a committee through deliberation. The implementation process is carried out entirely online and forms an IT team to support the smooth running of the implementation process. The evaluation process of the committee prepares activity reports to analyze changes in the implementation of activities using the diagram method. (2) The response of stakeholders through the implementation of the zoning system in improving the quality of schools at SMA Negeri 2 Palopo received a positive response with 65% of prospective students being accepted through the zoning route which helped reduce the gap between superior and disadvantaged schools. (3) Stakeholder obstacles through the implementation of the zoning system in improving the quality of schools at SMA Negeri 2 Palopo show that there is a lack of socialization and during the registration process, there are technical problems such as network connections that are lost due to slow servers and errors.